The Use Of Social Media Influencers in Digital Marketing to Target Consumer Buying Interest - Caesar Octoviandy Purba; Heny Handayani (STIE AMKOP, 2022)
Communication and relationship building have become easier thanks to technological advances such as social media apps. One of the offenders that contribute to the success of digital marketing platforms such as social media is the use of influencers. Effective marketing entails keeping a product in front of consumers' minds so that they choose to purchase the products on offer. The goal of this study is to find out how digital marketing via social media influencers influences consumer purchasing behavior. According to AISAS streams, micro-influencers, macro-influencers, and mega-influencers can create content that piques the interest of many netizens. The number of likes and comments on an influencer's account can indicate how popular the account is with followers. Influencers can also use their visual style to communicate various types of promotions and personal jargon This is exemplified by appealing photography and copywriting. It is obvious that affected netizens have the potential to search for products (search), buy products (action), and review products, which can have an impact on companies that can promote their products to influencers. As a result, influencer marketing has grown in popularity as a marketing strategy for influencers because they can present posts that promote brand image and characteristics that have a significant impact on their consumers.